Investigation of in vitro antioxidant and Cytotoxic potential of Methanolic extract of celosia Argentea leaves - Mitu, Nusrat Jahan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.